Practical Implications of Parabolas - Sah, Shivam Kumar; Sahani, Suresh Kumar; Sahani, Kameshwar (Sigma&Mu: Journal of Mathematics, Statistics and Data Science, 2025)
This project highlights the significance of parabolas in technology, science, and architecture while examining their various everyday uses. Because they can concentrate sound waves at a particular location, parabolic shapes are essential in the construction of satellite dishes, automobile headlights, and flashlights. This project illustrates how mathematics and practical problem-solving structural stability and visual appeal. This project illustrates how mathematics and practical problem solving interact by jamming the uses of parabolas, showing how a straightforward geometric shape can transform technology and enhance everyday life.